Arbuscular mycorrhizal fungi as a bio-indicator of soil health under agricultural management practices in South Africa - Sekgota, Wendy Maphefo (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology, 2019)
This study investigated the activity of arbuscular mycorrhizal (AM) fungi as a potential biological indicator of soil health under conventional and conservation agricultural management in South Africa. An experimental trial consisting of three replicates plots under conventional and reduced tillage subdivided into twelve treatments of six crops and two fertilizer inputs was assessed over four growing seasons for various AM fungal parameters such as spore density, most probable number (MPN) of propagules percentage root colonisation and easily extractable glomalin (EEG). Cropping combinations were maize monoculture; maize soybean rotation; maize cowpea rotation; maize cowpea intercropping; maize oats intercropping and maize vetch intercropping. Resident AM fungal spore numbers and EEG protein levels were very low and no root colonization was recorded in the first two growing seasons. These findings prompted the need for the inoculation of the study site in the third growing season with a commercial AM fungal product (MycorootTM). Spore numbers, EEG concentrations and percentage root colonisation increased 8 weeks after inoculation but were significantly reduced in the fourth growing season that was not inoculated. MPN infectivity increased with inoculation particularly under conventional tillage and maize monoculture. Resident spore taxa were morphologically identified into three genera Gigaspora, Scutellospora, and Glomus. For the first two growing seasons, the maize roots were heavily colonized by a pathogenic fungus after mycorrhizal inoculation no evidence of pathogenic fungi was observed. In the fourth growing season which did not receive inoculation, root colonization started to decline. Reduced tillage, high fertilizer input combined with maize cowpea rotation (MC) and maize hairy vetch intercropping (Mv) had a significant effect (P = 0.01) on AM fungal spore numbers. Cropping systems and high fertilizer input had a significant effect on EEG concentrations in the second growing season. Overall, fertilizer application and crop type had implications for mycorrhizal activity. The soil health status in this study site was deemed low as measured by the impaired mycorrhizal activity due to agricultural management practices. Field inoculation combined with classical and molecular tools could provide a more realistic assessment of the effect of agricultural management practices on AM fungi as potential bioindicators of soil health. Therefore, AM fungi could be used as bioindicators of soil health under agricultural management practices in South African soil conditions.
Keywords: Soils -- Quality -- South Africa; Soil fertility -- South Africa; Fungi in agriculture -- South Africa; Mycorrhizal fungi; Vesicular-arbuscular mycorrhizas; Fungi -- Spores; Soils -- Agricultural chemical content